Effects and action mechanisms of lotus leaf (Nelumbo nucifera) ethanol extract on gut microbes and obesity in high-fat diet-fed rats - Yanan, Zhang; Lu, Ma; Lu, Zhang; Jinhai, Huo; Weiming, Wang (Frontiers in Nutrition, 2023)
ABSTRACT Objective: To clarify the effect of the lotus leaf ethanol extract (LLEE) on the mechanism of anti-obesity and the intestinal microbiota of obese rats. Methods: Forty SPF male SD rats were split into blank group model group, Orlistat capsule group, LLEE group. All the groups were intervened and fed for five months. During the experiment, we evaluated the body weight, length, serum biochemical indicators and inflammatory factor levels of the rats. After dissection, the liver, epididymal and perirenal WAT, and the contents of cecum were collected for pathological evaluation and intestinal flora analysis. Results: Lotus leaf alcohol extract can significantly reduce the serum total cholesterol, triglyceride, and low-density lipoprotein cholesterol levels. It also decreases the accumulation in the liver of fatty rats, the levels of serum inflammatory factors IL-6 and TNF-α, and increase the level of IL-10. Lotus leaf alcohol extracts significantly increased the abundance of Muribaculaceae in the intestinal flora of rats, reduced the abundance of pro-inflammatory bacteria Frimicutes, and relieved fatty liver and other inflammation and diseases caused by high-fat diet. Besides, the ethanol extract of lotus leaf significantly regulated the abundance of Ruminococcus, suggesting that the ethanol extract of lotus leaf may have the effect of preventing hyperlipidemia. Conclusions: We elucidated the effects and action mechanisms of LLEE on obesity in high-fat diet-fed rats, to provide suggestions for regulating intestinal flora through dietary intervention, and thus improving blood lipid metabolism.